2014
DOI: 10.1016/j.acap.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Career Satisfaction Among Pediatric Hospitalists: A Qualitative Exploration

Abstract: Objectives To characterize determinants of career satisfaction among pediatric hospitalists working in diverse practice settings, and to develop a framework to conceptualize factors influencing career satisfaction. Methods Semi-structured interviews were conducted with community and tertiary care hospitalists, using purposeful sampling to attain maximum response diversity. We employed close- and open-ended questions to assess levels of career satisfaction and its determinants. Interviews were conducted by te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
13
1
Order By: Relevance
“…Perhaps more interestingly, unlike previous studies, 6,10 the most frequently cited motivator for community pediatric hospitalists in our study was professional impact, a theme that consists exclusively of nonclinical subthemes. We found that there are ample opportunities for career growth at community sites, including in the areas of scholarship and leadership.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Perhaps more interestingly, unlike previous studies, 6,10 the most frequently cited motivator for community pediatric hospitalists in our study was professional impact, a theme that consists exclusively of nonclinical subthemes. We found that there are ample opportunities for career growth at community sites, including in the areas of scholarship and leadership.…”
Section: Discussioncontrasting
confidence: 83%
“…6 In a different study, researchers found that community PHM physicians prioritized resource availability, work schedules, and clinical responsibilities over nonclinical responsibilities and career development. 10 Although the physicians in our study were also motivated by work-life integration and various clinical responsibilities as seen in the themes of personal and professional satisfaction and scope of practice, income was not mentioned as a motivating factor.…”
Section: Discussionmentioning
confidence: 69%
“…At GHs, research and QI efforts focused on common conditions are needed to increase our knowledge of contextually relevant barriers to and facilitators of high‐quality pediatric care. This, however, can be made more difficult by small sample sizes, limited resources, and infrastructure, and competing priorities in adult‐focused GH settings . Multihospital learning collaboratives and partnerships between FCHs and GHs can begin to address these challenges, but their success is contingent upon national advocacy and funding to support pediatric research and quality measures at GHs.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalists working at community hospitals may experience several unique opportunities and challenges, including limited pediatric-specific equipment and skills among non-hospitalist colleagues, increased needs to advocate to administration for child health, and needs to address pediatric safety and quality improvement in adult-oriented settings. 15,17,18 PHM fellowship training can provide valuable skills for addressing these opportunities, provided that there is flexibility in the fellowship curricula to support training across the structurally diverse hospitals where children receive hospital care. 19 Relative to residents entering subspecialty fellowships, we found that residents' family situation, geographic location preferences, and level of educational debt were strongly associated with decisions to enter PHM.…”
Section: Discussionmentioning
confidence: 99%